1990
DOI: 10.1182/blood.v75.8.1606.bloodjournal7581606
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow transplantation for acute myelocytic leukemia in first remission: a European survey of the role of marrow purging

Abstract: We analyzed data from 263 patients with acute myelocytic leukemia (AML) autografted in first remission (CR) during the period from January, 1982 to January, 1987 at one of 34 centers in the European Bone Marrow Transplant Group. The median age of patients was 30 years (range, 1 to 65). The median interval between achieving CR and autografting was 5 months (range, 1 to 23). Of the 263 patients, 131 patients received cytoreductive regimens that included total body irradiation (TBI); the remainder received variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 1 publication
2
35
0
Order By: Relevance
“…Several studies have demonstrated that mafosfamidepurged autografts, although deprived of cycling progenitors, are capable of reconstituting hematopoietic function due to the property of mafosfamide to spare noncycling stem cells [25,26]. The addition of SCF to a growth factor combination including G-CSF, GM-CSF, IL-3 and EPO has been found to be critical for in vitro proliferation of quiescent primitive progenitors surviving marrow purging with mafosfamide [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that mafosfamidepurged autografts, although deprived of cycling progenitors, are capable of reconstituting hematopoietic function due to the property of mafosfamide to spare noncycling stem cells [25,26]. The addition of SCF to a growth factor combination including G-CSF, GM-CSF, IL-3 and EPO has been found to be critical for in vitro proliferation of quiescent primitive progenitors surviving marrow purging with mafosfamide [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…High-dose therapy with autologous stem cell transplantation (ASCT) is an effective treatment option for selected patients with haemopoietic malignancies and solid tumours (Gorin et al, 1990;Coiffier et al, 1993). An obstacle to this approach is that the reinfusion of clonogenic tumour cells contained in the autograft could contribute to relapse of disease (Brenner et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Over 70% of patients with follicular lymphoma have an aberrant translocation chromosome, t(14;18)(q32;q21) harboring the bcl-2 gene in juxtaposition to the immunoglobulin heavy chain (IgH) locus, a rearrangement detectable at diagnosis by polymerase chain reaction (PCR) [5][6][7]. Immunologic and pharmacologic purging of harvested bone marrow sufficient for delivery of PCRnegative progenitor cells has been shown to increase relapse-free survival [8,9]. Unless these additional treatment options are instituted, such occult lymphoma cells may subsequently contribute to disease relapse, especially in patients with advanced follicular lymphomas in whom overt marrow infiltration is commonly seen [10,11].…”
Section: Introductionmentioning
confidence: 99%